Atrial flutter mimicking ST‐elevation myocardial infarction. Issue 3 (6th May 2021) - Kumar, Sundeep; Mogalapalli, Akhil; Bedi, Rohil; Mar, Philip L.
Abstract : A 12 lead electrocardiogram provides an important diagnostic tool for atrial flutter recognition. However, rarely, atrial flutter waves can cause diagnostic challenges by producing ST segment abnormalities mimicking ST segment elevation and result in unnecessary workup and treatment. ​